Single mothers and child support in extended-family households: An international perspective - Angela Guarin; Merita Mesiäislehto; Mia Hakovirta; Molly Costanzo (Luxembourg Income Study (LIS), 2023)
Extended-family households are a common arrangement among single mothers in various countries. Using Luxembourg Income Study data from waves 2014-2019, we study child support receipt among single mothers living in extended-family households in Chile, Guatemala, Panama, Paraguay, Peru, Spain, the United States, and Uruguay. We have three aims: (1) to present the prevalence and characteristics of single mothers living in extended-family households; (2) to compare the level of child support received by extended-family and other single-mother households; and (3) to examine whether living in an extended-family household is a predictor of child support receipt across countries. We find the characteristics of mothers in extended family households vary by country. Overall, mothers in extended family households are more likely to be younger, have lower levels of education, are less likely to be employed, and are somewhat less likely to receive child support compared to other single mothers.
Keywords: 330; Child support; single mothers; extended families; Latin America